Exploring the Impact of Family Structure on Child Development - Ratu Indira (Mahogany Journal De Social, 2024)
This looks at examines the impact of circle of relative’s shape on baby improvement outcomes, using descriptive facts and comparative evaluation. The sample encompasses various circle of relative’s compositions, consisting of nuclear families, unmarried-figure families, blended families, and same-intercourse determine households. Child development consequences, especially related to emotional functioning, are assessed the use of standardized measures. Results monitor a heterogeneous distribution of family systems inside the pattern, reflecting present day family compositions. Variability in infant improvement consequences is determined throughout distinct circle of relative’s structures. Comparative evaluation with previous studies underscores the nuanced interplay between own family structure and baby properly-being. The findings emphasize the importance of tailored interventions, culturally sensitive approaches, and interdisciplinary research to sell high-quality outcomes for youngsters throughout diverse own family contexts.